Development and validation of the Workplace Relational Needs Satisfaction Scale (W-RNSS) - Hanc, Veronika; Žvelc, Gregor; Bajec, Boštjan (Frontiers in Psychology, 2024)
While inadequate relationships in the workplace pose a significant psychosocial risk, quality interpersonal relationships can contribute to positive effects and prevent negative outcomes. Erskine's model of relational needs, not yet studied in the work environment, can provide a more detailed understanding of the needs employees experience in their workplace relationships. We adapted the general Relational Needs Satisfaction Scale (RNSS) for coworker relationships and examined the factor structure of relational needs in the workplace and their connections to various work aspects. The sample comprised 273 participants, including both employees and students, in a workplace setting with coworkers. The results show that the Workplace Relational Needs Satisfaction Scale (W-RNSS) is a valid and reliable instrument (α = 0.93 for the total scale and 0.77 < α < 0.89 for the subscales) for measuring relational needs in coworker relationships. A bifactor model was the most suitable for describing the data (χ2/df = 1.94, CFI = 0.95, TLI = 0.94, NNFI = 0.94, RMSEA = 0.06, SRMR = 0.04, AIC = 13289.27, BIC = 13506.29), confirming the previously supported 5factor structure and the general factor. Satisfaction of relational needs was associated with higher work satisfaction, increased work engagement, greater motivation and lower burnout, underscoring the importance of quality interpersonal relationships among employees. W-RNSS shows potential for researching connections with other work aspects and practical applications in prevention and intervention strategies.